A comprehensive review on harvesting of microalgae using Polyacrylamide-Based Flocculants: Potentials and challenges - Shifa M.R. Shaikh (17128882) (2021)
Microalgae biomass is touted as a highly promising source of renewable third-generation biofuels that could enable a lucrative transition from conventional fossil fuels to more sustainable and environment-friendly energy alternatives. A significant limiting step for large-scale microalgae production and utilization is harvesting and dewatering the cultivated biomass, which comprise 20–30% of the total production expenses. Compared to traditional physical harvesting methods, coagulation-flocculation techniques using polyacrylamide-based flocculants have garnered attention as promising alternatives due to their high harvesting efficiencies, cost-effectiveness, convenience, and scalability. This paper delivers an up-to-date progress in the harvesting of microalgae suspensions using various polyacrylamide flocculants. For the first time, a comprehensive evaluation of existing harvesting studies for freshwater and marine microalgae species using polyacrylamide-based flocculants was conducted. The impact of polyacrylamide-based flocculant characteristics (e.g., charge type, charge density, polymer architecture, molecular weight) on flocculation efficiencies was examined. The effect of the culture medium properties (e.g., pH, salinity, microalgae species, microalgae growth phase, cell density, flocculation aids) on polyacrylamide-induced flocculation was also evaluated. Existing pilot-scale and large-scale polyacrylamide-based flocculation studies were explored. The review further identifies the research gaps, key challenges and future prospects for optimizing microalgae flocculation studies. Other Information Published in: Separation and Purification Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.seppur.2021.119508